Inimputabilidad de los adolescentes infractores en la ley orgánica de transporte terrestre tránsito y seguridad vial y su incidencia en el cometimiento de delitos en el cantón Vinces - Jordán Yépez, Luis Eduardo (2019)
The imputability of adolescent offenders disposed in international laws and conventions is a very controversial issue in the legislation of many countries. The increase in serious traffic offenses, news from other Latin American countries mention the increase in traffic infractions, where children under 18 are involved, either as perpetrators or accessories, they are leading the society to propose new alternatives in the legal field, educational partner to mitigate the increase of the criminal boom of adolescents who violate the traffic law, which will benefit the international community. The location of the non-attribution of adolescent offenders in the structure of the commission of crimes concerned will be studied in accordance with the organic law of land transport and road safety in the canton of Vinces, as well as the action liberae in cause, the elements of the non-criminality and the reasons for this, which come to be the lack of mental development or mental immaturity, transient mental disorder, lack of mental health, serious fear, well-founded fear, some legal scholars consider intoxication and drug addiction, a subject that will study to know why or why it should not be considered as a reason for unimpeachable. All these causes generate negative effects before the opinion of the vinceña community, to its institutions in charge of guaranteeing the control and public order, the human, material losses, to causing mutilation of the family, which causes commotion to society. The foundation of the exemption is the inability to know and value since that capacity is achieved through education and coexistence in society. Such situation can be motivated by the deaf-mutism or by any other original or supervening cause. This incapacity does not allow perceiving and logically assessing the acts, that is, it is a situation similar to the ignorance of the Law, that is, the "impossibility of knowledge or assumption of unlawfulness.